2013
DOI: 10.1002/ejoc.201300324
|View full text |Cite
|
Sign up to set email alerts
|

A Concise and Efficient Total Synthesis of Oleocanthal

Abstract: Oleocanthal, one of the minor components of the phenolic fraction isolated from extra virgin olive oil, is an effective inhibitor of COX enzymes, possessing similar potency to the NSAID ibuprofen. Moreover, it has the capacity to alter the structure of neurotoxic Aβ‐amyloid oligomers (ADDLs) and to change the structure of deformed microtubule‐associated tau–protein, thus inhibiting the formation of neurofibrillary tangles. It can have, therefore, potential therapeutic use for the treatment of neurodegenerative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…For in vivo studies, higher amounts of the compound are needed. The synthesis of OLC requires about ten steps and the yields remain quite low (Smith, Sperry & Han, 2007;English & Williams, 2009;Takahashi, Morita & Honda, 2012;Valli et al, 2013). Thus, isolation of OLC from natural sources (olive oil, olive oil pomace, olive leaves or olive oil mill waste water) is an important option.…”
Section: Introductionmentioning
confidence: 99%
“…For in vivo studies, higher amounts of the compound are needed. The synthesis of OLC requires about ten steps and the yields remain quite low (Smith, Sperry & Han, 2007;English & Williams, 2009;Takahashi, Morita & Honda, 2012;Valli et al, 2013). Thus, isolation of OLC from natural sources (olive oil, olive oil pomace, olive leaves or olive oil mill waste water) is an important option.…”
Section: Introductionmentioning
confidence: 99%
“…OC was first discovered in 1992 [ 20 , 21 ], and its chemical structure was revealed by Montedoro et al in 1993 [ 22 ]. Chemical synthesis of OC has been attempted by several research groups [ 23 , 24 , 25 , 26 , 27 ]. Natural OC exists in the S-configuration of chiral carbon, while synthetic OC is present in the R-configuration [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, chemical synthesis of OLC has been tried by several laboratories (English & Williams, 2009;Smith 3rd, Han, Breslin, & Beauchamp, 2005;Valli et al, 2013) and different analogue compounds were synthesized by tyrosol esterification and carbamoylation. Natural OLC exists in the S-configuration of chiral carbon, whereas synthetic OLC is present in the R-configuration (Beauchamp et al, 2005;Cicerale, Breslin, et al, 2009).…”
Section: Chemical Structure Of Oleocanthalmentioning
confidence: 99%
“…In 2003, Andrewes et al reported that OLC is the sole phenolic compound responsible for the throat irritant sensation and pungency induced by EVOO (Andrewes, Busch, de Joode, Groenewegen, & Alexandre, 2003), and it was named OLC ( oleo‐ for olive, canth‐ for sting, and ‐ al for aldehyde) (Beauchamp et al, 2005; Cicerale, Breslin, et al, 2009). Thereafter, chemical synthesis of OLC has been tried by several laboratories (English & Williams, 2009; Smith 3rd, Han, Breslin, & Beauchamp, 2005; Valli et al, 2013) and different analogue compounds were synthesized by tyrosol esterification and carbamoylation. Natural OLC exists in the S‐configuration of chiral carbon, whereas synthetic OLC is present in the R‐configuration (Beauchamp et al, 2005; Cicerale, Breslin, et al, 2009).…”
Section: Chemical Structure Of Oleocanthalmentioning
confidence: 99%